FERRITIN nanocages used as programmable bricks for biomolecular electronics - Luis, Lechaptois (Nanyang Technological University, 2024)
Ferritin nanocages are ubiquitous proteins, widely known for their ability to handle iron atoms inside many living species. This particular protein has a unique architecture made of an amino acid shell with an iron core and has appeared as an attractive candidate to be incorporated into an electrical device (junction, solid-state transistor). The goal is to characterise the electrostatic properties, charge states, and interactions with a semi-conductor surface of ferritins for biomolecular electronics. Furthermore, the overall surface of ferritin (naturally negatively charged) can be modulated through bioengineering techniques (site-directed mutagenesis) to be positively charged. During this thesis, the ferritin nanocages were produced and bioengineered in the NTU laboratory in Singapore, and were characterised in solution using light scattering techniques (ELS, DLS). The mutations of the ferritins were performed by substitution of negative amino acids with positive ones, and the ferritin mutants showed a shift in their isoelectric point (IEP). In order to study the electrostatic behaviour of the ferritin proteins on a solid surface, they were deposited on a doped silicon substrate, and the sample surfaces were scanned by Kelvin Probe Force Microscopy (KPFM), which is an advanced technique of the atomic force microscopy that simultaneously measures the topography and the surface potential of a sample surface. The characterisation of ferritin immobilized on a silicon surface by KPFM reveals a change in the ferritin morphology (flattening) and electrostatics properties (surface potential) as a function of their iron content. Moreover, these results present a new method to determine the orientation and conformality of proteins directly on a solid surface by measuring their electric dipole. For the mutated ferritins, the surface potential measured by KPFM showed no change in the sign of the surface charge (from negative to positive), but significant changes are noticeable and indicate the modulation of the surface charge of the mutated ferritins. This study gives strong insight into the possible incorporation of the ferritin inside electronic devices. For this, other electrostatic interactions remain to be studied when a nanoparticle is deposited on a semi-conductor such as the formation of a Schottky barrier, which was investigated during this thesis with a model particle (50 nm gold nanoparticles) deposited on silicon and measured by KPFM. Based on the electrostatic study of the ferritin (and gold nanoparticles), one of the next ideas would be to achieve an active mixed monolayer of positive and negative ferritin that will be deposited onto a pseudo-MOSFET structure. The change in the positive/negative particle ratio will modulate the source-drain current.